2011
DOI: 10.1111/j.1365-2966.2010.18007.x
|View full text |Cite
|
Sign up to set email alerts
|

Density perturbations in a gas of wormholes

Abstract: The observed dark matter phenomenon is attributed to the presence of a gas of wormholes. We show that due to topological polarization effects, the background density of baryons generates non-vanishing values for wormhole rest masses. We infer basic formulae for the scattering cross-section between baryons and wormholes and equations of motion. Such equations are then used for the kinetic and hydrodynamic description of the gas of wormholes. In the Newtonian approximation, we consider the behaviour of density p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…In particular, our attempts to describe dark matter phenomena by wormholes [26,27] owe to this feature. Indeed, if we have a point source M at some position z 0 (the density is ̺ = M √ g δ(z − z 0 )), then the condition (10) produces a countable set of "additional" sources (̺ → ̺ = M √ g n δ(z − e na z 0 )) and this essentially changes the "expected" standard Newton's potential produced by the source, while the transformation δ(z − z 0 ) → n δ(z − e na z 0 ) we call the topological bias of sources.…”
Section: Stable Relic Wormholesmentioning
confidence: 98%
“…In particular, our attempts to describe dark matter phenomena by wormholes [26,27] owe to this feature. Indeed, if we have a point source M at some position z 0 (the density is ̺ = M √ g δ(z − z 0 )), then the condition (10) produces a countable set of "additional" sources (̺ → ̺ = M √ g n δ(z − e na z 0 )) and this essentially changes the "expected" standard Newton's potential produced by the source, while the transformation δ(z − z 0 ) → n δ(z − e na z 0 ) we call the topological bias of sources.…”
Section: Stable Relic Wormholesmentioning
confidence: 98%
“…In the present review, we do not take into account the fact that, in general, wormholes possess non-vanishing masses M. In the problem of scattering of radiation, the masses of wormholes produce a number of additive effects, which can be considered separately. In particular, they determine light deflection and are also important when considering the back reaction (e.g., in removing cusps in galaxies [12]). However such additive effects are identical to those produced by standard forms of matter, and, therefore, they do not allow us to distinguish wormholes.…”
Section: The Simplest Model Of a Wormholementioning
confidence: 99%
“…Basic elements of relativistic kinetic theory can be found in standard textbooks, for example, [20]; see also [12]. We let f (r, p, t) be the number of particles in the interval of the phase space dΓ = d 3 rd 3 p. This function obeys the equation…”
Section: Boltzmann Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…We point out that gas of actual (astrophysical) wormholes was first investigated in a series of papers [6][7][8] where we have demonstrated that actual wormholes may be responsible for the dark matter phenomenon. Unlike astrophysical wormholes virtual wormholes exist only for very small period of time and at very small scales.…”
Section: Introductionmentioning
confidence: 98%